Traffic safety in urban underground road systems - Yeung, Jian Sheng (2015)
As the urbanisation phenomenon continues to manifest itself, cities are faced with the challenge of urban sustainability. One key issue is the land space constraint, calling for urban space creation. To overcome space limitations, many cities are beginning to utilise urban underground space for various uses, and underground road systems are acknowledged to be a strategic use, especially in highly developed areas. As underground road systems become increasingly popular, it is important to understand how traffic performance is affected in a road tunnel environment. However, there is limited knowledge available in the literature, especially for traffic safety in urban road tunnels. Hence, the objective of this research is to investigate traffic safety in urban underground road systems. The research adopted a multilevel approach to evaluating traffic safety in urban underground road systems. At the macroscopic level, studies in the literature suggest that traffic accident rates in road tunnels are lower than those on open roads but more information is needed to characterise traffic accidents in urban road tunnels. Road traffic accidents (RTAs) that occurred in urban expressway tunnels in Singapore were examined for a 3-year period (2009-2011) and interestingly it was found that after disaggregating the RTAs by zone, travel direction, and crash type, RTA rates were excessively higher at the tunnel portals, especially on tunnel entry. More than two in three tunnel RTAs were rear-end collisions, indicating that inter-vehicle interactions in urban road tunnels required further investigation at the mesoscopic and microscopic levels. At the mesoscopic level, car-following behaviour and drivers’ visual attention were examined to establish the link between driver behaviour and RTA risk. Car-following behaviour in an urban expressway tunnel was compared with that in an urban open expressway and it was found that drivers had more conservative behaviour in the road tunnel environment. Headways were longer and overall safety margins were higher in the expressway tunnel. In addition, other factors affecting car-following behaviour such as lane, leader type, and speed were investigated in both open and tunnel road environments. Drivers’ eye movement data in the same urban expressway tunnel were obtained from an on-road study. Glance behaviour was compared between the tunnel entry zone and the tunnel interior zone, based on one-minute epochs of data. The results revealed that drivers made more glances to the in-vehicle dashboard and the forward roadway in tunnel entry compared to the tunnel interior, resulting in shorter glances and overall glance time to the forward roadway. Less attention was paid to the forward roadway in tunnel entry, explaining the higher RTA risk at tunnel portal areas. On the microscopic level, driver perception was investigated to understand how it may modulate driver behaviour. A free association study was conducted and driver perspectives of open and tunnel expressways were found to be different based on associations to various roadway qualities. Drivers perceived speed, traffic condition, and scenery to be most prevalent for open expressways; while lighting, enforcement, and safety were most prevalent for tunnel expressways. This implied that drivers in road tunnel environments were more likely to exhibit safer driving behaviour than in open road environments. However, the reported quality of experience in tunnel expressways was lower than that in open expressways, meaning that there is room for improvement for the design of urban road tunnels. Also, a driver task load index survey was conducted to find out how drivers perceived the driving task in the tunnel expressway. Compared to the open expressway, drivers perceived driving in road tunnels to be more mentally demanding and required more effort. Overall, the findings show that the implementation of urban underground road systems is justifiable in term of traffic safety and should be recommended. Macroscopic evaluation revealed that RTA rates in road tunnels were lower than those in open roads, which was due to safer car-following behaviour as shown through mesoscopic analyses. The safer behaviour was likely the result of safety-oriented perspectives of the road tunnel environment and drivers being more vigilant in road tunnels, as found in the microscopic assessment. In addition, traffic safety at tunnel portals can be enhanced by improving the design of the road tunnel to help reduce the need for drivers to look away from the forward roadway.